Factors Influencing Renal Impairment in HIVs Infected Patients Receiving Antiretroviral Drugs - จันเทร์มะ, สิริลักษณ์; ชุมนิรัตน์, อนิวัต; อนุมาศ, นฤมล; ธีระกุล, วารณี; แซ่ลิ่ม, อภิรดี (Journal of Health Science of Thailand, 2022)
HIV-infected patients having abnormal kidney function (CKD stage 2-5) might due to the long period, continuous consumption of antiretroviral drugs which results in renal insufficiency. This study aimed to investigate factors influencing renal insufficiency in HIV-infected patients receiving antiretroviral therapy. A retrospective cohort study was conducted. Characteristics of HIV patients and renal insufficiency were collected from the HIV clinic of Hatyai hospital, southern Thailand. A total of 556 HIV-infected patients who received antiretroviral drugs were collected from patients’ medical records and the hospital database during fiscal years 2013 to 2018. Descriptive statistics analysis was performed. Chi-square test was used to find the association between factors and renal insufficiency and logistic regression was used to find the strength of association. Renal insufficiency after receiving antiretroviral therapy at the level of 3-5 was identified in 34 patients (6.1%). Factors affecting renal insufficiency were age, CD4 levels, receiving another antiretroviral drugs formula and having high blood pressure. Renal insufficiency was higher among patients aged 50 years and older, having CD4 level less than 200 cells/µL, and having high blood pressure. In conclusion, preventing renal insufficiency by adjusting the optimal dose of drug together with health promotion should be emphasized among HIV patients aged 50 years and older, having CD4 less than 200 cells/µL and having high blood pressure.